2014
DOI: 10.3945/ajcn.113.082826
|View full text |Cite
|
Sign up to set email alerts
|

Low-calorie sweeteners and body weight and composition: a meta-analysis of randomized controlled trials and prospective cohort studies , ,

Abstract: Background: Replacement of caloric sweeteners with lower- or no-calorie alternatives may facilitate weight loss or weight maintenance by helping to reduce energy intake; however, past research examining low-calorie sweeteners (LCSs) and body weight has produced mixed results.Objective: The objective was to systematically review and quantitatively evaluate randomized controlled trials (RCTs) and prospective cohort studies, separately, that examined the relation between LCSs and body weight and composition.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
202
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(220 citation statements)
references
References 60 publications
(182 reference statements)
5
202
1
12
Order By: Relevance
“…The proportion of participants with HbA1c levels ≤7% in this study was lower than that of the studies done in France and Spain [31,32]. In terms of comparison of the study results with that of the Al-Rowais' study of type II diabetes patients conducted in the Kingdom of Saudi Arabia [33], the percentage of participants who obtained acceptable HbA1c levels (6-8%) was almost the same.…”
Section: Discussionmentioning
confidence: 40%
“…The proportion of participants with HbA1c levels ≤7% in this study was lower than that of the studies done in France and Spain [31,32]. In terms of comparison of the study results with that of the Al-Rowais' study of type II diabetes patients conducted in the Kingdom of Saudi Arabia [33], the percentage of participants who obtained acceptable HbA1c levels (6-8%) was almost the same.…”
Section: Discussionmentioning
confidence: 40%
“…Systematic reviews, including meta-analyses, of these studies show that LCS compared to sugar reliably reduces energy intake and body weight (18,19) . For the most recent meta-analysis of effects on body weight participants were adults and children (n = 1332) and the duration of the intervention and any follow-up varied from 4 weeks to 40 months (19) .…”
Section: Evidence From Human and Animal Studiesmentioning
confidence: 99%
“…A recent meta-analysis of NNS studies in both adults and children reported that RCTs demonstrated potential health benefits, including modest weight loss and weight maintenance, whereas observational studies showed a small but significant association with increasing BMI. 12 That review was conducted in the absence of an a priori protocol, and the published search strategy was incomplete. 29 Our review addressed these limitations and aimed to evaluate a broader scope of metabolic health outcomes (beyond weight gain and body composition) focusing on long-term effects and including prenatal exposures.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…10,11 Sugar replacements or nonnutritive sweeteners (NNSs) have thus gained enormous popularity owing to their low caloric value and perceived health benefits. 10,12 The consumption of beverages and foods containing NNSs has increased markedly in recent decades, 10 particularly in children, 13 yet their long-term impact on human health is unclear, and current recommendations for NNS use during pregnancy and childhood are conflicting. Although the American Dietetic Association maintains that NNSs are safe in pregnant women and children within acceptable daily intakes, 14 the Institute of Medicine does not support NNS use in children, citing "a paucity of evidence on longterm health effects … from [NNSs], particularly resulting from exposure initiated in childhood."…”
mentioning
confidence: 99%